Estudo da eficiência do processo de coagulação/floculação e do processo combinado de coagulação/floculação/adsorção para tratamento de águas residuárias de galvanoplastia utilizando Moringa oleífera - Alves, Alvaro Cesar Dias (2012)
This study aimed to evaluate the efficiency of the process of coagulation/ flocculation and coagulation/flocculation/adsorption combined process for treatment of liquid effluent from the electroplanting industry. Were used the moringa seed as a natural coagulant agent and moringa bark and string bean as adsorbents. Were evaluated the parameters COD, color, pH, turbidity and the concentration of metal ions Cr, Zn, Cu and Ni. In the stage of coagulation/ flocculation were used several concentrations of moringa in salt solution of NaCl 1 M and 0.1M. In the stage of the combined adsorbents were used moringa bark and string beans to determine which of the adsorbent had a better removal efficiency of metals. Tests were also conducted with different ranges of mass for the best adsorbent and variation of pH of the studied effluent. Tests of coagulation/flocculation showed good removal efficiency for the parameters COD, Color, Turbidity and the metals Cr, Zn, Cu and Ni using MO seed in salt solution 1M, these values being 90.49%, 78.34%, 95.13%, 25.29%, 84.30%, 51.11% and 24.74% respectively. In the tests of coagulation/flocculation/adsorption the maximum removal efficiencies were 91.41% for COD, 90.77% for color, 95.31% for Turbidity, 58.36% for Cr, 98.36% for Zn, 97,58% for Cu and 99.11% for Ni. The research showed that after the combined process the electroplanting effluent did not present the necessary characteristics for the released in to water bodies due to the high remaining concentration of Cr (1907.4 mg/L), Color (860 PtCo/L) and COD (330 mg/L). The research for the treatment process demonstrated great effectiveness for most parameters analyzed, however, its necessary to study complementary technologies for this type of treatment effluent in order to achieve an effluent within the release standards into the water bodies.